The Responsiveness of Fiqh and Its Local Wisdom of Pengajian Pitulasan Menara Kudus - Munawaroh, Lathifah; Abdillah, Junaidi (LPPM IAIN Kudus, 2022)
The characteristics of fiqh with its local wisdom in the Pengajian Pitulasan are based on the charismatic authority approach of Sunan and Kiai figures who gave a philosophical view named Gusjigang. Gusjigang is a dialectic reflection between fiqh and local wisdom in Kudus city. This philosophy is applied in daily life which leads to being a completely human character. The form of responsiveness fiqh found in the Pengajian Pitulasan Yayasan Menara Kudus is to use the method and approach of qauli by involving dialogical elements that reflect the public mind even though it is still at a small level. This research is a type of field research based on literature review as know as library research with the documentary-historical method. The data also shows that the form of fiqh responsiveness in the Pengajian Pitulasan has absorbed various dimensions of life such as the economic, social, health, and other fields. Among the forms of fiqh that represent the dialectic between fiqh and its local wisdom in the Pengajian Pitulasan are: the role of the Kiai is clearly seem in preserving the local culture of Pengajian Pitulasan Yayasan Menara Kudus and avoiding sacrifices with the cow for the Kudus Kulon community.